A cysteine-clamp gene drives embryo polarity in the midge Chironomus - Klomp, Jeff; Lemke, Steffen (Science. First release, 2015)
How to generate head-to-tail polarity in a midge Animal genomes do not remain static but gain and lose essential genes over time. One such case is the bicoid gene of flies. Bicoid plays an important role in early Drosophila development during the generation of head-to-tail polarity, but most flies lack bicoid. Which genes then serve the same function in other insects? Now, Klomp et al. report a structurally unrelated gene that serves essentially the same function as bicoid in a mosquito-related midge but does so through a different genetic mechanism. Science, this issue p. 1040 In the fruit fly Drosophila, head formation is driven by a single gene, bicoid, which generates head-to-tail polarity of the main embryonic axis. Bicoid deficiency results in embryos with tail-to-tail polarity and no head. However, most insects lack bicoid, and the molecular mechanism for establishing head-to-tail polarity is poorly understood. We have identified a gene that establishes head-to-tail polarity of the mosquito-like midge, Chironomus riparius. This gene, named panish, encodes a cysteine-clamp DNA binding domain and operates through a different mechanism than bicoid. This finding, combined with the observation that the phylogenetic distributions of panish and bicoid are limited to specific families of flies, reveals frequent evolutionary changes of body axis determinants and a remarkable opportunity to study gene regulatory network evolution. Structurally unrelated genes in fly and a mosquito-related midge serve the same function by different mechanisms. Structurally unrelated genes in fly and a mosquito-related midge serve the same function by different mechanisms.